2021
DOI: 10.35341/afet.992596
|View full text |Cite
|
Sign up to set email alerts
|

İzmir Kent Yerleşiklerinin Temel Afet Bilgi ve Bilinç Düzeyinin Ölçülmesi

Abstract: Çalışmanın temel hedefleri İzmir ili yerleşiklerinin afetler konusundaki temel bilgi ve bilinç düzeyinin ölçülmesi ve bu veriler ışığında kamu kurum ve kuruluşlarının yapacakları bölgesel afet planlarına sayısal veriler oluşturmaktır. Bu amaç doğrultusunda çalışmada ulusal ve uluslararası alandaki afet tanımları açıklandıktan sonra İzmir ili yerleşikleriyle yapılan anket görüşmesinin sonuçlarına yer verilmiştir. Çalışma nitel araştırma yöntemi olarak kabul edilen yazılı dokümanların incelenmesi ve nicel araştı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
2
1
0
2
Order By: Relevance
“…It was determined that there was no statistically significant difference between the disaster experience variable and both disaster awareness (p>0.05) and disaster preparedness (p>0.05). There are parallel results with the findings obtained in the study: Aras et al, (2021) in their study between disaster awareness and earthquake experience, Demirci (2021) in Izmir province between disaster experience and disaster awareness, Ertuğrul and Ünal (2020) found that there was no statistical difference between disaster preparedness beliefs and disaster experience. Contrary to these results, Dikmenli and Yakar (2019) found the level of awareness of those who experienced disasters to be higher.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It was determined that there was no statistically significant difference between the disaster experience variable and both disaster awareness (p>0.05) and disaster preparedness (p>0.05). There are parallel results with the findings obtained in the study: Aras et al, (2021) in their study between disaster awareness and earthquake experience, Demirci (2021) in Izmir province between disaster experience and disaster awareness, Ertuğrul and Ünal (2020) found that there was no statistical difference between disaster preparedness beliefs and disaster experience. Contrary to these results, Dikmenli and Yakar (2019) found the level of awareness of those who experienced disasters to be higher.…”
Section: Discussionsupporting
confidence: 83%
“…It can be said that both disaster awareness and disaster preparedness levels of Vocational School students are at a good level. When the literature on disaster awareness studies is examined, there are studies that support the findings of our study (Şahin et al, 2018;Tekin and Dikmenli, 2021) and studies that have different results from our findings (Dikmenli and Yakar, 2019; URL 1; Ozkazanc and Yuksel, 2015;Bhat et al, 2017;Avcı et al, 2020;Oyanık and Cengiz, 2020;Demirci, 2021). When the literature on disaster preparedness studies is examined, there are studies that support our findings (Aslantaş and Tabuk, 2021) and differ from our findings (Ağahan, 2018;Koçak, 2004;Tanner and Doberstein, 2015; URL 1; Ozkazanc and Yuksel, 2015;Şahin et al, 2018;Dinçer and Kumru, 2021;Hasan et al, 2022).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Ulusal Medikal Kurtarma Ekipleri (UMKE) üzerinde yapılan bir araştırmada yaş değişkeni ile afet hazırlığı arasında anlamlı bir farkın olduğu belirtilmiştir (Ünal vd., 2017). Bireyler üzerinde yapılan başka bir çalışmada ise yaş değişkeni ile afet hazırlığı arasında anlamlı bir farkın olduğu ve 18-25 yaş arasındaki bireylerin afet konusundaki bilgi ve bilinç düzeyinin yüksek olduğu tespit edilmiştir (Demirci, 2021). Bu iki çalışmada elde edilen sonucun araştırma sonucu ile benzer olduğu görülmektedir.…”
Section: Bulgular Ve Tartişmaunclassified
“…Öğretmen adayları üzerinde yapılan bir çalışmada ise öğrenim düzeyi artıkça afet algı ve bilinç düzeyinin arttığı tespit edilmiştir (Dikmenli ve Yakar, 2019). İzmir'de yaşayan bireyler üzerinde yapılan başka bir çalışmada ise öğrenim düzeyi yükseldikçe bireylerin bilgi ve bilinç düzeyinin yükseldiği saptanmıştır (Demirci, 2021). Afetlere karşı hazırlıklı olmak için bireylerin dolayısıyla toplumun eğitim düzeyinin yüksek olmasının önemli bir kriter olduğu söylenilebilir.…”
Section: Bulgular Ve Tartişmaunclassified